Analisis Deskriptif Pengetahuan Tentang Perubahan Fisik Pubertas Remaja Putri di Pondok Pesantren Alfalah Sofaniyah Kecamatan Songgom Kabupaten Brebes Tahun 2024 - Utami, Suci; Meikawati, Pedvin Ratna; Fajriyah, Laeli Fitrokhatun (JURNAL KESEHATAN TERAPAN, 2024)
Puberty imarks ithe itransition ifrom ichildhood ito iadolescence iaccompanied iby ia iseries iof icomplex iphysical, icognitiveiand ipsychological idevelopmental iprocesses. iThere iare istill imany iyoung iwomen iwho ido inot iknow ithe idevelopment iofipuberty. iLack iof iknowledge iabout ipuberty ican ihave ia inegative iimpact ion ithe idevelopment iof iadolescent igirls. iThisitype iof iresearch iuses iquantitative idescriptive ianalysis imethods. The data collection process uses a questionnaire method with a Guttman scale. From the results of research on 39 research samples of adolescent girls at the Al Falah Sofwaniyah Jatirokeh Islamic Boarding School, the results showed that 25 girls (64%) had knowledge of puberty in the "Good" category. 11 children (28%) had knowledge of puberty in the "Enough" category. 3 children (8%) had knowledge of puberty in the "Poor" category. With these data it can be concluded that the majority of young women at the Al Falah Sofwaniyah Jatirokeh Islamic Boarding School have good knowledge about puberty.